2013
DOI: 10.1002/ar.22819
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Primary Cilia Distribution and Morphology During Lactation, Stasis, and Involution in the Bovine Mammary Gland

Abstract: Primary cilia are small, sensory organelles projecting from virtually all cells and are vital for cellular and tissue function. Their distribution in bovine mammary tissue has not previously been assessed, despite the potential for these organelles to provide specialized perceptive and regulatory functions to this acutely responsive and adaptive gland. The research objectives were to assess ciliary distribution and morphology during active lactation, milk stasis, and early involution using tissue samples obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 75 publications
2
7
0
Order By: Relevance
“…Furthermore, studies in vivo demonstrated that acute physical distension of rat mammary glands with sucrose solution accelerated the induction of apoptosis, upregulation of the apoptotic factor activated signal transducer and activator of transcription-3, and loss of the extracellular matrix factor β1-integrin and tight junction factor occludin (Phyn et al, 2007). Recently, the distribution and morphological changes in the mechanosensors primary cilia during lactation and involution implicate a role in initiating involution of the mammary gland (Millier et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, studies in vivo demonstrated that acute physical distension of rat mammary glands with sucrose solution accelerated the induction of apoptosis, upregulation of the apoptotic factor activated signal transducer and activator of transcription-3, and loss of the extracellular matrix factor β1-integrin and tight junction factor occludin (Phyn et al, 2007). Recently, the distribution and morphological changes in the mechanosensors primary cilia during lactation and involution implicate a role in initiating involution of the mammary gland (Millier et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…In support of mechanotransduction, mammary cell stretch in vitro induces apoptotic pathways (Quaglino et al, ) and in vivo accelerates the induction of apoptosis and loss of the ECM factor β1‐integrin and the TJ protein occludin (Phyn et al, ). Furthermore, primary cilia, key signalling organelles for sensing biochemical and biophysical extracellular stimuli, have been implicated in initiating involution of the mammary gland (Millier et al, ; Biet et al, ).…”
mentioning
confidence: 99%
“…In the total fraction, the percentage of ciliated cells was the same in the lactation and 7-d NM groups, but was increased (P < 0.1) in the 28-d NM group compared with the lactation group (Figure 4). Nevertheless, the average depth of Z-stacks was 1.5 μm, whereas the tissue sections were 7 μm, both considerably less than the average width of a luminal SEC (Millier et al, 2013). Therefore, the proportion of cilia detected will most likely underestimate the actual biological incidence.…”
Section: Quantitative Analysis Of Pc Incidence and Orientationmentioning
confidence: 96%
“…In the bovine mammary gland, the presence of PC on SEC and MEC was first demonstrated by Nickerson (1989). More recently, PC incidence and celltype distribution and morphology have been described during lactation, milk stasis, and early involution, suggesting a potential mechanosensory role the bovine mammary gland (Millier et al, 2013).…”
Section: Introductionmentioning
confidence: 96%